PENINGKATAN HASIL BELAJAR MENGGUNAKAN MEDIA FLASH CARD MATERI PEMBELAHAN SEL DI SMA NEGERI 1 SUMBER - arum hidayati (Tunas Nusantara, 2023)
The purpose of this research is to improve the students of XII 3 Mathematics and Science learning result about the Cell Fission on the First Semester of 2022/2023 Academic Year by using Flash Card media. This is a Classroom Action Research (CAR). The subjects are 35 students; consist of 6 boys and 29 girls. The action on the learning is using Flash Card media on the cooperative learning. The tool of learning output evaluation is the daily test, consist of 20 multiples questions. The colleague is validating on the learning planning, work sheet for the learning and tool of learning output evaluation. The research is going on two cycles. The result is learning result about the Cell Fission improving. On the Former Condition, learning results are 69 on the average (not good) and 57,14% on the classical completeness (not good). On the First Cycle, learning results are 75,14 on the average (good enough) and 77,14% on the classical completeness (moderate). On the Second Cycle, learning results are 81,71 on the average (good) and 88,57% on the classical completeness (good).Kata Kunci: Learning Output, Flash Card, Cell Fission